FAKTOR-FAKTOR YANG MEMPENGARUHI SETORAN LPPL RADIO PADA LPPL RADIO KABUPATEN/KOTA SE-JAWA TENGAH (Proceeding Fakultas Ekonomi, 2014)
This study aims to analyze the factors that affect deposit LPPL (Local Public Broadcasting) Radioon Radio LPPL Regency/City in Central Java. Some researchers emphasize the effect of the regulation isa factor, the budget ceiling given by the budget, the number of HR employees and deposit targetsmandated by the respective local government district/city. The population in this study was 32 LPPLRadio districts/cities in Central Java. In addition, this study uses panel data time series for the past threeyears, starting in 2011, 2012 and 2013. This study uses multiple methods approach, the approaches are :Pooled Least Square (PLS), Fixed Effect Model (FEM) and Random Effect Model (REM). The modeltesting uses Chow Test and Hausman Test. The hypothesis testing, conducted through partial test basedon t test. The results showed that model tends to use FEM. Based on that estimation model was found thatonly two variables that were significant namely regulation and deposit targets at 5% significance level.Beside that amaount of human resources was significant at 10% significance level. The rest that is thebudget was insignificant.Keywords: Deposits of LPPL Radio, budgets, HR